Mesenchymal stem cells for treating autoimmune dacryoadenitis - Xiaoxiao Lu (Stem Cell Research & Therapy, 2017)
Abstract Autoimmune dacryoadenitis, such as Sjögren syndrome, comprises multifactorial and complex diseases. Inflammation of the lacrimal gland plays a key role in the pathogenesis of diseases. Unfortunately, current treatment strategies, including artificial tears, anti-inflammatory drugs, punctual occlusion, and immunosuppressive drugs, are only palliative, and long-term administration of these strategies is associated with adverse effects that limit their utility. Hence, an effective and safe treatment for autoimmune dacryoadenitis is urgently needed. Mesenchymal stem cells (MSCs) have emerged as a promising tool for treating autoimmune dacryoadenitis, owing to their immunosuppressive properties, tissue repair functions, and powerful differentiation capabilities. A large number of studies have focused on the effect of MSCs on autoimmune diseases, such as autoimmune uveitis, inflammatory bowel disease, and collagen-induced arthritis, but few studies have, to date, unequivocally established the efficacy of MSCs for treating autoimmune dacryoadenitis. In this review, we discuss recent advances in MSC treatment for autoimmune dacryoadenitis.